2019
DOI: 10.1002/adfm.201808294
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Local Structural Ordering and Chemical Distribution upon Delithiation of a Rock Salt–Structured Li1.3Ta0.3Mn0.4O2 Cathode

Abstract: Lithium-rich disordered rock-salt oxides have attracted great interest owing to their promising performance as Li-ion battery cathodes. While experimental and theoretical efforts are critical in advancing this class of materials, a fundamental understanding of key property changes upon Li extraction is largely missing. In the present study, single-crystal synthesis of a new disordered rock-salt cathode material, Li 1.3 Ta 0.3 Mn 0.4 O 2 (LTMO), and its use as a model compound to investigate Li concentration-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…We present our approach for handling the 3D imaging results on Li x Ta 0.3 Mn 0.4 O 2 battery cathode particles that tilted slightly during the acquisition of the spectro-tomographic data (Kan et al, 2019). We focused on the Mn K edge because the redox activity of the Mn cation in this material is one of the major charge-compensation mechanisms for the cathode during battery operation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We present our approach for handling the 3D imaging results on Li x Ta 0.3 Mn 0.4 O 2 battery cathode particles that tilted slightly during the acquisition of the spectro-tomographic data (Kan et al, 2019). We focused on the Mn K edge because the redox activity of the Mn cation in this material is one of the major charge-compensation mechanisms for the cathode during battery operation.…”
Section: Resultsmentioning
confidence: 99%
“…The sample was then washed with acetonitrile several times and dried overnight. For more details, we refer to the published literature (Kan et al, 2019).…”
Section: Sample Preparationmentioning
confidence: 99%
“…In contrast, the structural failure in Li-ion battery mainly occurs during the Li-ion extraction process when an enormous particle pulverization takes place, as shown in Figure 6 Similar to 2D TXM, tomography can be combined with XAS technique in order to obtain a 3D chemical mapping. In a recent 3D XANES study, tomography measurements with 30 nm resolution were conducted to study the delithiation of micro-sized Li1.3Ta0.3Mn0.4O2 (LTMO) cathode particles [68]. The imaging data was collected at more than 100 energy points across the Mn K-edge to create a 3D chemical map, as shown in Figure 7 (a).…”
Section: D Tomography Imaging Based On Txmmentioning
confidence: 99%
“…[18] Kan et al have reported a continuous decrease in the short-range order of Ta during delithiation of Li 1.3 Ta 0.3 Mn 0.4 O 2 cathode material, implying the existence of a certain driving force that increases a degree of disorder in multi-component Li-excess systems. [19] Although further study is needed, one possible answer may reside in the local separation that induces significant inhomogeneous strain and concentration of stress within the crystallite, which may have facilitated the cation-disorder process.…”
Section: Electrochemical Performance and Carbon-coated Lmcomentioning
confidence: 99%